GREEN INNOVATION AND ENVIRONMENTAL SUSTAINABILITY: IMPLICATIONS FOR BUSINESS MANAGEMENT - Febriana, Widia; Komala, Rina; Hayati, Ridha Nurul; Angelita, Sacila Agrizkiana (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The growing urgency of climate change and resource depletion has positioned environmental sustainability as a central concern in contemporary business management. Green innovation, which integrates ecological considerations into products, processes, and organizational strategies, has become a critical driver for firms seeking both competitiveness and responsibility. This paper explores the implications of green innovation for business management practices, emphasizing how organizations can balance environmental goals with economic performance. Drawing on recent literature and global case examples, the study highlights three key dimensions: the role of sustainable supply chains, the integration of green technologies, and the influence of corporate governance in fostering eco-friendly initiatives. The findings suggest that businesses adopting green innovation not only reduce environmental risks but also enhance long-term resilience, strengthen stakeholder trust, and create new market opportunities. However, challenges such as high implementation costs, limited regulatory alignment, and resistance to organizational change remain significant barriers. For managers, the implications extend beyond compliance, requiring a reconfiguration of strategic planning, investment decisions, and performance measurement systems. This paper concludes that embedding green innovation within business management is not merely a response to external pressures but an essential pathway to sustainable growth and competitive advantage in the global economy.